Estrutura, desenvolvimento e alimentação do Brycon Devillei Castelnau, 1855 (Pisces-Characidae) - Correa, Veronica Lima da Silva (1980)
Present an analyses of the altertions in the struture, development and feeding habits of the species Brycon devillei Castelnau,1855, from Lago Dom Helvécio wich is part of the system of lakes of the Parque Florestal do Vale do Rio Doce in Minas Gerais. This alterations were: the change from a long narrow body in the young to a broader one in the adult; the change from carnivorous,with canines teeth in the young phase to herbivorous, with molar teeth with tree or more cuspids in the adult. The observations of behavior of this species in Lago Dom Helvécio demonstrated that the young phases prefer shallow margens and live in heterotipic communities of small fishes on wich they feed. The adult,wich migrates in fluvial ambients circles the margens of the lake constantly,proving its equal capacity of adaptation a lentic habitat.